From exception to pioneering: Insights on combining professional autonomy and social rights from the Syndicat National des Artistes Plasticien·nes - Mathilde Mondon-Navazo; Annalisa Murgia (Cuadernos de Relaciones Laborales, 2024)
This article contributes to the limited research on solo self-employed (SSE) workers, who strive to collectively address social and labour rights issues while preserving their autonomy. It examines a unique case within the French context, the Syndicat National des Artistes Plasticien·nes (SNAP), a trade union created in 1977 within the Confédération Générale du Travail (CGT) to represent self-employed visual artists. Through extensive ethnographic research conducted both online and offline, the study explores how SSE artists organise collectively to improve their access to social rights while protecting their autonomy, which is particularly crucial for creative workers. The findings show how SSE workers can unite to advocate for social protection while redefining the promise of professional autonomy embedded in the so-called ‘enterprise culture’. Additionally, it sheds light on an early example of SSE workers organising, which may provide useful insights for other groups of SSE workers, who are rapidly growing across Europe.